Optimizing corporate governance: unraveling the interplay of board structure and firm efficiency - Muhammad Farooq Shabbir; Hassan Danial Aslam; Elaine Yen Nee Oon; Aamir Amin (Cogent Economics & Finance, 2024)
This study investigates the relationship between board characteristics and firm efficiency in emerging Asian economies, using stochastic frontier analysis and a panel dataset of 5829 firm-year observations. The results suggest that companies with strong monitoring boards concerning diversity, size, and independence achieve higher efficiency. This study provides more specific results on the importance of board characteristics for firm-level governance and highlights the Asian emerging markets' focus on good governance practices. The study's use of firm efficiency as a proxy for performance is a unique framework that mitigates endogeneity issues common in corporate governance variables. This approach is an improvement over previous research that has relied on financial ratios, which need to consider the value of management's actions and investment decisions affecting future performance. The results contribute to the literature on corporate governance and provide valuable insights for investors in emerging markets.
Keywords: 330; Board characteristics; efficiency; emerging markets; board index; shareholder's rights